Novel derivatives of 3D woven T-shaped composites with improved performance. Issue 2 (1st February 2019) - Ali, Mumtaz; Kausar, Faizan; Shahid, Salma; Zeeshan, Muhammad; Nawab, Yasir; Riaz, Rabia; Memon, Anam Ali; Mengal, Naveed; Anjum, Aima Sameen
Abstract: Conventional 3D woven T-shaped preforms were modified for improving joint/ peel off strength of associated T-shaped polymeric composites. Preforms were modified at weaving level by preferred yarns orientations for better performance in associated composites. Major modifications studied are; the addition of supporting layer, single or double-crossing in joint layers and crossing along with supporting layer (in a single sample). Novel derivatives were compared with conventionally used (on-loom and off-loom) T-shaped 3D woven composites. Microscopic analysis was also carried out to analyze the orientation of yarns and analysis of samples from failure point after testing. By combined variation of crossing and supporting layers improvement of 47.37% in peel off strength and 70.37% in impact strength was observed. Modified T shapes can serve to be a good replacement for conventional T-shaped stiffener (used to avoid folding under loads) and in joints.